A kind of fluidized bed hydroprocessing catalyst and preparation method thereof
Through hydrothermal reaction synthesis of phthalite and sol molding technology, high-strength and low-wear boiling bed hydrogenation catalyst particles were prepared, solving the problems of easy breakage and complex preparation of existing catalysts. It is suitable for inferior quality with high metal impurity content. Heavy oil treatment achieves efficient hydrotreatment.
Patent Information
- Application Number
- CN202211437532.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-17
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-11-17
Smart Images

Figure BDA0003947313200000101
Abstract
Description
Technical Field
[0001] The invention relates to an ebullated bed hydroprocessing catalyst and a preparation method thereof, in particular to an ebullated bed hydroprocessing catalyst suitable for heavy oil, especially inferior heavy oil with high metal content and a preparation method thereof. Background Art
[0002] With the gradual reduction of oil resources, the increasing demand for light oil and increasingly stringent environmental regulations, the oil refining industry attaches great importance to the rational use of resources, which has greatly promoted the development of heavy oil hydroprocessing technology. Heavy oil hydroprocessing technologies mainly include fixed bed, ebullating bed, suspended bed and moving bed. Fixed bed has been widely used due to its mature technology and simple operation. However, the fixed bed hydrogenation of residual oil has strict restrictions on the metal and carbon content in the raw materials. The ebullating bed residual oil hydrogenation is conducive to maintaining high catalyst activity and long-term operation because the catalyst can be added and discharged online. It has strong adaptability to raw materials and flexible processing schemes. It can process inferior raw materials with high metal impurity content, such as vacuum residue oil, and has a very broad application prospect.
[0003] During the ebullating bed hydrogenation process, the crude oil and hydrogen flow upward through the catalyst bed, the bed expands, and the catalyst particles are in an irregular motion state in the reactor, that is, a "boiling" state. Therefore, the catalyst is required to have not only high hydrogenation and conversion activity, but also high crushing strength and wear resistance, because the catalyst is regularly added and removed from the reactor under high temperature and high pressure, and the catalyst is always in a violent boiling state in the reactor, with more collision and friction opportunities, easy to break and wear, and increased catalyst consumption will have an adverse effect on downstream equipment. In addition, there are certain requirements for the bulk density, particle shape, and particle size distribution of the catalyst. It is generally believed that the more suitable particle shape is a spherical particle with a small particle size. Spherical particles are easy to flow, maintain a boiling state in the reactor, require a small fluid velocity, and do not have sharp, rough corners that are easily crushed in other shapes.
[0004] At present, industrial hydroprocessing catalysts are usually based on alumina carriers, with Group VIII and Group VIB metal elements as active components. The preparation methods of spherical particle carriers mainly include: spray drying molding, rolling molding, oil molding, etc.
[0005] Spray drying molding is to use an atomizer to disperse the raw material slurry into droplets and dry the droplets with hot air. Spray molding requires fine atomized droplets. Therefore, the microspheres (several microns or tens of microns) prepared by spray molding are suitable for catalytic cracking catalysts. Rotational molding is to send powder and an appropriate amount of water (or other binders) into a container rotating at a low speed. The powder particles agglomerate together under the action of liquid bridge and capillary force to form micronuclei, which are constantly rotating and growing in the powder layer, and finally become spherical particles of a certain size. However, the density of the rotationally molded particles is not high and the strength is poor. Oil molding is to use the gelation characteristics of the sol at an appropriate pH value and concentration. The sol is dripped into a medium such as kerosene in the form of small droplets. Due to the action of surface tension, it shrinks into a ball and then gels to form small particles. However, this method is difficult to prepare microspheres with smaller particle sizes.
[0006] Patent application number CN02146394.8 discloses a method for forming spherical alumina, which includes dripping alumina sol into an oil-ammonia column consisting of an upper oil phase of 0.1 to 4.5 mm and a lower electrolyte solution phase of 10 to 300 mm to form spherical gel particles, and then aging the gel particles in the electrolyte solution phase for 0.5 to 10 hours, and then drying and calcining. The prepared spherical alumina particles are 1 to 2 mm, and it is difficult to prepare microspheres with smaller particle sizes by this method.
[0007] CN 113663683A discloses a method for preparing a series-type inferior heavy oil boiling bed hydrogenation catalyst, which comprises a spherical pre-hydrogenation demetallization catalyst and a spherical main hydrogenation catalyst which are used in series. The method for preparing the spherical pre-hydrogenation demetallization catalyst comprises the following steps: at room temperature, aluminum hydroxide powder containing zirconium and mixed rare earth elements is placed in a drum of a ball rolling machine, and a dilute mixed acid solution containing aluminum elements is sprayed into the drum under rotation. The powder in the drum forms microspheres under the action of the acid solution containing aluminum elements. Under the action of the centrifugal force of the drum, aluminum hydroxide powder containing zirconium and mixed rare earth elements is continuously added, and the dilute mixed acid solution containing aluminum elements is continuously sprayed. The drum speed is controlled at 40 to 50 revolutions / min. min, after reacting for 20 minutes, aluminum hydroxide powder balls containing zirconium and mixed rare earth elements are obtained; the aluminum hydroxide powder balls containing zirconium and mixed rare earth elements are transferred from the drum of the ball rolling machine to a cylindrical polishing machine for polishing and drying, and the dried balls are loaded into a sagger roasting furnace and roasted at a temperature of 700-800°C for 4 hours to obtain alumina ball carriers containing zirconium and mixed rare earth elements; the alumina ball carriers containing zirconium and mixed rare earth elements are loaded into the stainless steel drum of the spray machine, and rotated and sprayed with a complex aqueous solution containing nickel, molybdenum and lanthanum elements at room temperature. After completion, the zirconium-containing alumina balls sprayed with nickel, molybdenum and lanthanum elements are transferred to a drying oven and heated at a temperature of 110-150°C. The spherical pre-hydrogenation demetallization catalyst is prepared by the following steps: placing aluminum hydroxide powder containing silicon and boron in a drum of a ball rolling machine at room temperature, spraying a dilute acid aqueous solution containing aluminum and phosphorus elements into the drum while the drum is rotating, and the aluminum hydroxide powder containing silicon and boron forms microspheres under the action of the dilute acid aqueous solution containing aluminum and phosphorus elements. With the continuous addition of aluminum hydroxide powder containing silicon and boron elements and the continuous spraying of the dilute acid aqueous solution containing aluminum and boron elements, the volume of the microspheres gradually increases to form aluminum hydroxide powder balls containing silicon, boron and phosphorus elements, and controlling the drum speed at 40 to 50 revolutions per minute. After 15 minutes, aluminum hydroxide powder balls containing silicon, boron and phosphorus elements are obtained; the aluminum hydroxide powder balls are transferred from the drum of the ball rolling machine to a cylindrical polishing machine for polishing and drying. The dried balls are placed in a sagger calcining furnace and roasted at 550-650°C for 4 hours to obtain alumina ball carriers containing silicon, boron and phosphorus elements; the alumina ball carrier is placed in the stainless steel drum of the spraying machine, and the acidic aqueous solution containing nickel and molybdenum elements is rotated and sprayed at room temperature. The sprayed alumina balls are transferred to a drying oven, dried at 110-150°C for 4-5 hours, and then transferred to a sagger and roasted at 450-550°C for 3.5-4.5 hours to obtain a spherical main hydrogenation catalyst.The above two catalysts are both prepared by rotational molding, and the prepared particles are not dense and have poor strength. At the same time, the addition of the polishing step also increases the complexity of the preparation and increases the preparation cost.
[0008] CN 101240190B discloses an ebullating bed hydroprocessing catalyst and a preparation method thereof. The spherical carrier preparation process of the method is as follows: a catalyst carrier raw material with suitable humidity is made into particles of suitable size, and then the particles are spheroidized, and the spherical material is heated to form a spherical catalyst carrier. The process of making the catalyst carrier raw material into particles of suitable size is to pass the wet material through a screen under mechanical action to produce particles. Between the two processes of granulation and spheroidization, it is best to place the granular material for a period of time or run it at a low speed for a period of time in the spheroidizing device. The disadvantage of this patent is that it has high requirements for equipment and requires specific equipment, and the production process also has certain requirements for the dryness and wetness of the environment. Summary of the invention
[0009] In view of the deficiencies of the prior art, the present invention provides an ebullated bed hydroprocessing catalyst, which has the characteristics of suitable particle size, uniform particles, excellent performance, high strength and low abrasion.
[0010] Another object of the present invention is to provide a method for preparing an ebullated bed hydroprocessing catalyst, which has a simple process flow and high production efficiency.
[0011] The technical solution of the present invention is as follows:
[0012] An ebullating bed hydroprocessing catalyst, the catalyst particle diameter is 0.4-0.8 mm, and the particle size distribution is: the ball with particle diameter <0.4 mm is less than 2.5%, and the ball with particle diameter 0.4-0.8 mm is more than 92%;
[0013] The pore volume is 0.65-0.95 mL / g, the average pore size is >15.0 nm, and the pore size distribution is: pores with a pore size <15 nm account for <5%, and pores with a pore size of 15-30 nm account for 50%-70%;
[0014] Specific surface area is 140~180m 2 / g; catalyst attrition <0.15wt%;
[0015] The catalyst contains 3.0% to 20.0% of Group VIB metal oxide and 0.3% to 8.0% of Group VIIl metal oxide.
[0016] Preferably, the catalyst contains 6.0% to 18.0% of Group VIB metal oxide and 0.5% to 5.0% of Group VIIl metal oxide.
[0017] The present invention provides a method for preparing an ebullated bed hydroprocessing catalyst, comprising the following steps:
[0018] (1) Aluminum oxide, aluminum hydroxide, an alkaline auxiliary agent and deionized water are prepared into a suspension, and a wet filter cake A is obtained by liquid grinding, hydrothermal reaction, washing and filtering;
[0019] (2) taking a certain amount of wet filter cake A obtained in step (1), adding deionized water, a peptizing agent solution, and a dispersant solution to prepare a sol B having a certain alumina content;
[0020] (3) the sol B prepared in step (2) is continuously injected at a certain flow rate into a column containing an upper layer of oil and a lower layer of alkaline solution to form the formed product, and the formed product is dried and calcined to obtain a spherical carrier C;
[0021] (4) After the carrier obtained in step (3) is impregnated with active metal components, it is directly placed in a calcination furnace for calcination to obtain the ebullating bed hydrogenation catalyst of the present invention.
[0022] In step 1 of the present invention, the alumina crystal form is ρ- or χ-type; the aluminum hydroxide is one or more of diaspore, boehmite, bayerite, and diaspore, wherein the aluminum hydroxide provides 40% to 60% of the aluminum oxide in the synthetic pseudo-boehmite wet filter cake; the alkaline auxiliary agent is one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, and ammonia water.
[0023] In step 1 of the present invention, the aluminum oxide content in the suspension is 5 to 20 g / 100 ml, and the alkali content is 0.5 to 2 g / 100 ml; the grinding is performed by ball milling or sand milling, and the average particle size after grinding is 0.1 to 5 μm; the hydrothermal reaction conditions are a temperature of 150 to 320° C., a pH value of 9 to 13, and a reaction time of 6 to 48 hours; the washing is performed by using deionized water at 50 to 85° C. to wash the material to neutrality; the filtration is performed by using a filter press or other filtering equipment to filter out the deionized water in the material, so that the aluminum oxide content in the filter cake is 25% to 35%.
[0024] In step 2 of the present invention, the peptizing agent is one or more of nitric acid, citric acid, and acetic acid; the peptizing agent solution is an aqueous solution of a peptizing agent, wherein the mass fraction of the peptizing agent in the peptizing agent solution is 30% to 50%; the amount of the peptizing agent added is 2% to 8% of the aluminum oxide in the wet filter cake; the dispersant is an organic dispersant and an inorganic dispersant, and the dispersant solution is an aqueous solution of a dispersant, wherein the mass fraction of the dispersant in the dispersant solution is 5% to 15%; the amount of the dispersant added is 0.2% to 2% of the aluminum oxide in the wet filter cake; the amount of deionized water added is to ensure that the aluminum oxide content in the prepared sol B is 10% to 20%; and step 2 is carried out under stirring.
[0025] In step 2 of the present invention, the dispersant is preferably an organic dispersant, including methylpentanol, polyethylene glycol, cellulose derivatives, polyacrylamide, guar gum, polyethylene glycol esters of fatty acids, sodium lauryl sulfate, and triethylhexyl phosphoric acid.
[0026] In step 3 of the present invention, the injection rate of the sol B is 5 mL / min to 25 mL / min; the height of the oil layer is 2 / 3 to 3 / 4 of the total height of the oil layer and the alkaline solution layer, wherein a stirring device is provided in the oil layer, and the depth of the stirring paddle is 1 / 4 to 2 / 3 of the upper part of the oil layer; after the sol B enters the oil layer, the stirring device is started, and the stirring speed is controlled to be 1000 to 4000 rpm; the drying temperature is 100°C to 150°C, and the drying time is 2 to 8 hours; the roasting temperature is 750°C to 900°C, and the roasting time is 2 to 6 hours.
[0027] In step 3 of the present invention, the oil in the upper layer is one of white oil and diesel, wherein the viscosity of the oil is 10 mm 2 / s~30mm 2 / s; the alkaline solution is one or more of ammonia water, ammonium carbonate, sodium hydroxide and potassium hydroxide solution, wherein the pH value of the alkaline solution is 10-12.
[0028] In step 4 of the present invention, the impregnation method is any impregnation method in industry, such as saturated impregnation and vacuum impregnation; the roasting temperature is 400-600° C., preferably 400-550° C.; and the roasting time is 2-8 hours.
[0029] In step 4 of the present invention, the active metal component is one or more of Group VIB metals and / or Group VIII metals; wherein the Group VIB metals are generally Mo and / or W, and the Group VIII metals are generally Ni and / or Co.
[0030] The advantages and effects of the present invention are as follows:
[0031] Compared with the prior art, the ebullated bed hydroprocessing catalyst and the preparation method thereof of the present invention have the following advantages:
[0032] (1) The catalyst of the present invention uses ρ- or χ-type alumina as a raw material, and undergoes a hydrothermal reaction with an alkali at a certain temperature and pressure to synthesize pseudo-boehmite. While simplifying the preparation process of pseudo-boehmite, the prepared pseudo-boehmite has the characteristics of large grains, large pore volume, large pore size, and concentrated pore distribution. At the same time, the pseudo-boehmite prepared under hydrothermal conditions has good peptization solubility, so that the finally prepared catalyst has higher strength, which can ensure that the catalyst has a longer life.
[0033] (2) The catalyst of the present invention adds a dispersant during the preparation of the sol. When the sol is added to the oil at a certain flow rate, it is quickly dispersed into very small liquid droplets under the stirring of high shear force in the oil. The liquid droplets sink into the alkaline solution under the action of gravity and solidify into gel microspheres. At the same time, the size of the liquid droplets is controlled by adjusting the stirring speed, thereby overcoming the disadvantage that the droplet process cannot prepare microspheres.
[0034] (3) The catalyst of the present invention uses the pseudo-boehmite wet filter cake synthesized by hydrothermal reaction of ρ- or χ-type alumina as raw material, which saves the process of drying the pseudo-boehmite and then adding water to slurry during molding, simplifying the preparation process and manufacturing cost of the catalyst. At the same time, using the pseudo-boehmite wet filter cake as raw material also avoids the problem of low catalyst strength and high abrasion due to the decrease of the peptization index during the drying process of the pseudo-boehmite, so that the prepared catalyst has higher strength and lower abrasion.
[0035] (4) The catalyst carrier of the present invention is directly calcined after impregnation, so that the calcination process is carried out in a water vapor and air atmosphere, which is beneficial to the dispersion of active metals and also simplifies the preparation process and manufacturing cost of the catalyst.
[0036] (5) The preparation method of the catalyst of the present invention is simple, low-cost, and suitable for industrial application. DETAILED DESCRIPTION
[0037] The technical features and reaction effects of the present invention are further described below by way of examples, but are not limited to the examples.
[0038] In the present invention, the specific surface area and pore volume of the catalyst are determined by N2 adsorption method; and the content of the metal component is analyzed by spectrophotometry.
[0039] Example 1
[0040] To deionized water, 500 g of boehmite (alumina content of 62%) and 245 g of p-type alumina were added so that the alumina provided by the boehmite accounted for 55.9% of the alumina in the synthetic pseudo-boehmite wet cake. Then 70 g of sodium hydroxide was added to prepare a suspension with an alumina content of 11.1 g / 100 mL, an alkali content of 1.4 g / 100 mL, and a pH value of 11.3. The suspension was ground using a ball mill to obtain a slurry with a particle size of 2.0 μm. The slurry was hydrothermally reacted at a reaction temperature of 230°C and a reaction pressure of 17 kg for 8 hours. After the reaction, the slurry was washed with 60°C deionized water until neutral and filtered to obtain a wet cake with an alumina content of 32%.
[0041] Weigh 625 g of the wet filter cake, add 436 g of deionized water, 30 g of a 40% nitric acid solution and 20 g of a 10% polyethylene glycol solution under stirring to prepare a sol with an aluminum oxide content of 18%;
[0042] The sol was continuously injected into the upper layer with a viscosity of 15 mm at a flow rate of 25 mL / min. 2 / s, a column with white oil of 70 mm in height and a lower layer of 30 mm and ammonia water with a pH value of 11.2, and at the same time, a stirring device with a stirring paddle depth of 25 mm in the oil layer is started, and the stirring speed is controlled to be 2500 rpm for molding. The molded product is dried at 130°C for 5 h, and then calcined at 850°C for 3 h to obtain the microspherical catalyst alumina carrier A of the present invention.
[0043] A Mo-Ni-P solution was prepared according to a conventional method, and the carrier A was saturated with the Mo-Ni-P solution and calcined at 500° C. for 3 hours to obtain the catalyst Ac of the present invention. The catalyst properties are shown in Table 1.
[0044] Example 2
[0045] The rest is the same as Example 1, except that the added ρ-type alumina is replaced by χ-type alumina, and the alumina provided by boehmite is adjusted to 45% of the alumina in the synthetic pseudo-boehmite wet cake, to obtain the catalyst Bc of the present invention. The catalyst properties are shown in Table 1.
[0046] Example 3
[0047] The other steps are the same as those in Example 1, except that the depth of the stirring paddle in the oil layer is changed to a stirring device of 40 mm, and the stirring speed is changed to 3500 rpm, to obtain the catalyst Cc of the present invention. The catalyst properties are shown in Table 1.
[0048] Example 4
[0049] The rest is the same as Example 1, except that the amount of nitric acid solution added is changed to 20 g and the amount of polyethylene glycol solution added is changed to 30 g, and the Mo-Ni-P solution is changed to Mo-Ni for impregnation to obtain the catalyst Dc of the present invention. The catalyst properties are shown in Table 1.
[0050] Example 5
[0051] To deionized water, 322.6 g of diaspore (alumina content of 62%) and 200 g of p-type alumina were added so that the alumina provided by boehmite was 50% of the alumina in the synthetic pseudo-boehmite wet cake. 50 g of sodium hydroxide was then added to prepare a suspension with an alumina content of 8.0 g / 100 mL, an alkali content of 1.0 g / 100 mL and a pH value of 10.7. The suspension was ground using a ball mill to obtain a slurry with a particle size of 2.2 μm. The slurry was subjected to hydrothermal reaction at a reaction temperature of 280°C and a reaction pressure of 18.5 kg for 12 hours. After the reaction was completed, the slurry was washed with 75°C deionized water until neutral and filtered to obtain a wet cake with an alumina content of 28%.
[0052] Weigh 714.3 g of the wet filter cake, add 574 g of deionized water, 40 g of 35% acetic acid solution and 45 g of 8% polyacrylamide solution under stirring to prepare a sol with an aluminum oxide content of 15%;
[0053] The sol was continuously injected into the upper layer with a viscosity of 20 mm at a flow rate of 15 mL / min. 2 / s, a column with white oil of 70 mm in height and a lower layer of 30 mm and ammonia water of pH 10.8, and at the same time, a stirring device with a stirring paddle depth of 25 mm in the oil layer is started, and the stirring speed is controlled to be 1500 rpm for molding. The molded product is dried at 120°C for 7h and then calcined at 800°C for 4h to obtain the microspherical catalyst alumina carrier E of the present invention.
[0054] A Mo-Co-P solution was prepared according to a conventional method, and the carrier E was saturated with the Mo-Co-P solution and calcined at 450° C. for 4 hours to obtain the catalyst Ec of the present invention. The catalyst properties are shown in Table 1.
[0055] Comparative Example 1
[0056] Weigh 285.7 g (dry basis 70%) of commercially available pseudo-boehmite, add 775.4 g of deionized water, 30 g of 40% nitric acid solution and 20 g of 10% polyethylene glycol solution under stirring to prepare a sol with an alumina content of 18%;
[0057] The sol was continuously injected into the upper layer with a viscosity of 15 mm at a flow rate of 25 mL / min. 2 / s, a column with white oil of 70 mm in height and a lower layer of 30 mm and ammonia water with a pH value of 11.2, and at the same time, a stirring device with a stirring paddle depth of 25 mm in the oil layer is started, and the stirring speed is controlled to be 2500 rpm for molding. The molded product is dried at 130°C for 5 h, and then calcined at 850°C for 3 h to obtain the microspherical catalyst alumina carrier A of the present invention.
[0058] The carrier F was saturated with Mo-Ni-P solution and calcined at 500°C for 3 hours to obtain catalyst Fc. The catalyst properties are shown in Table 1.
[0059] Comparative Example 2
[0060] To deionized water, 500 g of boehmite (alumina content of 62%) and 245 g of p-type alumina were added so that the alumina provided by the boehmite accounted for 55.9% of the alumina in the synthetic pseudo-boehmite wet cake. Then 70 g of sodium hydroxide was added to prepare a suspension with an alumina content of 11.1 g / 100 mL, an alkali content of 1.4 g / 100 mL, and a pH value of 11.3. The suspension was ground using a ball mill to obtain a slurry with a particle size of 2.0 μm. The slurry was hydrothermally reacted at a reaction temperature of 230°C and a reaction pressure of 17 kg for 8 hours. After the reaction, the slurry was washed with 60°C deionized water until neutral and filtered to obtain a wet cake with an alumina content of 32%.
[0061] Weigh 625 g of the wet filter cake, add 446 g of deionized water and 30 g of 40% nitric acid solution under stirring to prepare a sol with an aluminum oxide content of 18%;
[0062] The sol was continuously injected into the upper layer with a viscosity of 15 mm at a flow rate of 25 mL / min. 2 / s, a column with white oil of 70 mm in height and a lower layer of 30 mm and ammonia water with a pH value of 11.2, and at the same time, a stirring device with a stirring paddle depth of 25 mm in the oil layer is started, and the stirring speed is controlled to be 2500 rpm for molding. The molded product is dried at 130°C for 5 h, and then calcined at 850°C for 3 h to obtain the microspherical catalyst alumina carrier A of the present invention.
[0063] The carrier G was saturated with Mo-Ni-P solution and calcined at 500°C for 3 hours to obtain catalyst Gc. The catalyst properties are shown in Table 1.
[0064] Table 1 Main physicochemical properties of catalysts
[0065]
[0066]
[0067] The properties of an ebullated bed hydroprocessing catalyst of the present invention are as follows:
[0068] The catalyst particle diameter is 0.4-0.8 mm, and the particle size distribution is: the spheres with particle diameters <0.4 mm account for <2.5%, and the spheres with particle diameters 0.4-0.8 mm account for >92%.
[0069] The pore volume is 0.65-0.95 mL / g, the average pore diameter is >15.0 nm, and the pore size distribution is: pores with a pore diameter of <15 nm account for <5%, and pores with a pore diameter of 15-30 nm account for 50%-70%.
[0070] Specific surface area is 140~180m 2 / g. Catalyst attrition <0.15wt%.
[0071] The catalyst contains 3.0% to 20.0% of Group VIB metal oxide (such as MoO3), preferably 6.0% to 18.0%, and 0.3% to 8.0% of Group VIIl metal oxide (such as NiO or CoO), preferably 0.5% to 5.0%. The catalyst may contain additives such as B, F, P, Si, and Ti according to the catalyst requirements, and the additive content is 0.2wt% to 3wt%.
[0072] The catalyst of the present invention can be used for hydrogenation treatment of heavy oil. The heavy raw oil can be any heavy oil or residual oil raw material. Generally, a heavy hydrocarbon raw material with a distillation range of more than 500° C. is used, which contains sulfur, nitrogen, asphaltene and a large amount of metal (such as V, Fe, Ni, Ca, Na, etc.) compounds, and the metal content is more than 150 μg / g. The operating conditions can be determined according to the properties of the raw materials and the required reaction effect. The reaction pressure is generally 8 to 25 MPa, the hydrogen-oil volume ratio is generally 100:1 to 1000:1, and the total liquid volume space velocity (LHSV, the ratio of the liquid phase feed volume to the total catalyst volume) is generally 0.1 to 5.0 h -1 The reaction temperature is generally 380-450°C.
[0073] Example 8
[0074] In step 1, the aluminum oxide content in the suspension is 5 / 100ml, and the alkali content is 0.5 / 100ml; the grinding is performed by ball milling or sand milling, and the average particle size after grinding is 0.1μm; the hydrothermal reaction conditions are temperature 150°C, pH value 9, and reaction time 6h; the washing is performed by using 50°C deionized water to wash the material to neutrality; the filtration is performed by using a filter press or other filtering equipment to filter out the deionized water in the material, so that the aluminum oxide content in the filter cake is 25%.
[0075] In step 2, the peptizing agent is one or more of nitric acid, citric acid, and acetic acid; the peptizing agent solution is an aqueous solution of a peptizing agent, wherein the mass fraction of the peptizing agent in the peptizing agent solution is 30%; the amount of the peptizing agent added is 2% of the aluminum oxide in the wet filter cake; the dispersant is an organic dispersant and an inorganic dispersant, and the dispersant solution is an aqueous solution of a dispersant, wherein the mass fraction of the dispersant in the dispersant solution is 5%; the amount of the dispersant added is 0.2% of the aluminum oxide in the wet filter cake; the amount of deionized water added is to ensure that the aluminum oxide content in the prepared sol B is 10%.
[0076] In step 3, the injection rate of the sol B is 5 mL / min; the height of the oil layer is 2 / 3 of the total height of the oil layer and the alkaline solution layer, wherein a stirring device is provided in the oil layer, and the depth of the stirring paddle is 1 / 4 of the upper part of the oil layer; after the sol B enters the oil layer, the stirring device is started, and the stirring speed is controlled to be 1000 rpm; the drying temperature is 100°C, and the drying time is 2h; the roasting temperature is 750°C, and the roasting time is 2h.
[0077] In step 3, the oil in the upper layer is one of white oil and diesel, wherein the viscosity of the oil is 10 mm 2 / s; the alkaline solution is one or more of ammonia water, ammonium carbonate, sodium hydroxide and potassium hydroxide solution, wherein the pH value of the alkaline solution is 10.
[0078] In step 4, the impregnation method is any impregnation method in the industry, such as saturated impregnation and vacuum impregnation; the roasting temperature is 400° C.; and the roasting time is 2 hours.
[0079] The other steps are the same as in Example 1.
[0080] Example 9
[0081] In step 1, the aluminum oxide content in the suspension is 20g / 100ml, and the alkali content is 2g / 100ml; the grinding is carried out by ball milling or sand milling, and the average particle size after grinding is 5μm; the hydrothermal reaction conditions are temperature 320°C, pH value 13, and reaction time 48h; the washing is to use 85°C deionized water to wash the material to neutrality; the filtration is to use a filter press or other filtering equipment to filter out the deionized water in the material, so that the aluminum oxide content in the filter cake is 35%.
[0082] In step 2, the peptizing agent is one or more of nitric acid, citric acid, and acetic acid; the peptizing agent solution is an aqueous solution of a peptizing agent, wherein the mass fraction of the peptizing agent in the peptizing agent solution is 50%; the amount of the peptizing agent added is 8% of the aluminum oxide in the wet filter cake; the dispersant is an organic dispersant and an inorganic dispersant, and the dispersant solution is an aqueous solution of a dispersing agent, wherein the mass fraction of the dispersant in the dispersant solution is 15%; the amount of the dispersant added is 2% of the aluminum oxide in the wet filter cake; the amount of deionized water added is to ensure that the aluminum oxide content in the prepared sol B is 20%.
[0083] In step 3, the injection flow rate of the sol B is 25 mL / min; the height of the oil layer is 3 / 4 of the total height of the oil layer and the alkaline solution layer, wherein a stirring device is provided in the oil layer, and the depth of the stirring paddle is 2 / 3 of the upper part of the oil layer; after the sol B enters the oil layer, the stirring device is started, and the stirring speed is controlled to be 4000 rpm; the drying temperature is 150°C, and the drying time is 8 hours; the roasting temperature is 900°C, and the roasting time is 6 hours.
[0084] In step 3, the oil in the upper layer is one of white oil and diesel, wherein the viscosity of the oil is 30 mm 2 / s; the alkaline solution is one or more of ammonia water, ammonium carbonate, sodium hydroxide and potassium hydroxide solution, wherein the pH value of the alkaline solution is 12.
[0085] In step 4 of the present invention, the impregnation method is any impregnation method in industry, such as saturated impregnation and vacuum impregnation; the roasting temperature is 600° C. and the roasting time is 8 hours.
[0086] The other steps are the same as in Example 1.
[0087] In step 1 of the present invention, the alumina crystal form is ρ- or χ-type; the aluminum hydroxide is one or more of diaspore, boehmite, bayerite, and diaspore, wherein the aluminum hydroxide provides 40% to 60% of the aluminum oxide in the synthetic pseudo-boehmite wet filter cake; the alkaline auxiliary agent is one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, and ammonia water.
[0088] In step 2 of the present invention, the dispersant is preferably an organic dispersant, including methylpentanol, polyethylene glycol, cellulose derivatives, polyacrylamide, guar gum, polyethylene glycol esters of fatty acids, sodium lauryl sulfate, and triethylhexyl phosphoric acid.
[0089] In step 4 of the present invention, the active metal component is one or more of Group VIB metals and / or Group VIII metals; wherein the Group VIB metals are generally Mo and / or W, and the Group VIII metals are generally Ni and / or Co.
[0090] For those skilled in the art, the above specific reagents are only a preferred embodiment of the present invention. It is obvious that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the principles or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention.
[0091] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing an ebullated bed hydroprocessing catalyst, characterized in that: The steps include: (1) Alumina, aluminum hydroxide, alkaline additive and deionized water are prepared into a suspension, and a wet filter cake A is obtained by liquid grinding, hydrothermal reaction, washing and filtering; (2) taking a certain amount of the wet filter cake A obtained in step (1), adding deionized water, a peptizing agent solution, and a dispersant solution to prepare a sol B having a certain alumina content; (3) the sol B prepared in step (2) is continuously injected at a certain flow rate into a column containing an upper layer of oil and a lower layer of alkaline solution to form the spherical carrier C; the formed product is dried and calcined to obtain the product; Wherein, a stirring device is provided in the oil layer, and the depth of the stirring paddle is 1 / 4 to 2 / 3 of the upper part of the oil layer; after the sol B enters the oil layer, the stirring device is started, and the stirring speed is controlled to be 1000 to 4000 rpm; (4) After the active metal component is impregnated into the carrier obtained in step (3), the carrier is directly placed in a calcination furnace for calcination to obtain an ebullated bed hydrogenation catalyst; The catalyst particles have a diameter of 0.4 to 0.8 mm, and a particle size distribution of: particles with a diameter of <0.4 mm have a sphere size of <2.5%, particles with a diameter of 0.4 to 0.8 mm have a sphere size of >92%; The pore volume is 0.65-0.95 mL / g, the average pore size is >15.0 nm, and the pore size distribution is: pores with a pore size <15 nm account for <5%, pores with a pore size of 15-30 nm account for 50%-70%; the specific surface area is 140-180 m 2 / g; catalyst attrition <0.15wt%; the catalyst contains 3.0% to 20.0% of Group VIB metal oxides and 0.3% to 8.0% of Group VIII metal oxides.
2. The method for preparing an ebullated bed hydroprocessing catalyst according to claim 1, characterized in that: The catalyst contains 6.0% to 18.0% of Group VIB metal oxides and 0.5% to 5.0% of Group VIII metal oxides.
3. The method for preparing an ebullated bed hydroprocessing catalyst according to claim 1, characterized in that: In the step (1), the alumina crystal form is ρ- or χ-type; the aluminum hydroxide is one or more of diaspore, boehmite, bayerite, and gibbsite, wherein the aluminum hydroxide provides 40% to 60% of the aluminum oxide in the synthetic pseudo-boehmite wet filter cake; and the alkaline auxiliary agent is one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, and ammonia water.
4. The method for preparing an ebullated bed hydroprocessing catalyst according to claim 1, characterized in that: In the step (1), the aluminum oxide content in the suspension is 5 to 20 g / 100 mL, and the alkali content is 0.5 to 2 g / 100 mL; the grinding is performed by ball milling or sand milling, and the average particle size after grinding is 0.1 to 5 μm; the hydrothermal reaction conditions are a temperature of 150 to 320° C., a pH value of 9 to 13, and a reaction time of 6 to 48 h; the washing is performed by using deionized water at 50 to 85° C. to wash the material to neutrality; the filtering is performed by using a filter press to filter out the deionized water in the material, so that the aluminum oxide content in the filter cake is 25% to 35%.
5. The method for preparing an ebullated bed hydroprocessing catalyst according to claim 1, characterized in that: In the step (2), the peptizing agent is one or more of nitric acid, citric acid, and acetic acid; the peptizing agent solution is an aqueous solution of the peptizing agent, wherein the mass fraction of the peptizing agent in the peptizing agent solution is 30% to 50%; the amount of the peptizing agent added is 2% to 8% of the aluminum oxide in the wet filter cake; the dispersant is an organic dispersant and an inorganic dispersant, and the dispersant solution is an aqueous solution of the dispersant, wherein the mass fraction of the dispersant in the dispersant solution is 5% to 15%; the amount of the dispersant added is 0.2% to 2% of the aluminum oxide in the wet filter cake; the amount of deionized water added is to ensure that the aluminum oxide content in the prepared sol B is 10% to 20%; and the step (2) is carried out under stirring.
6. The method for preparing an ebullated bed hydroprocessing catalyst according to claim 5, characterized in that: In the step (2), the dispersant is an organic dispersant, including methylpentanol, polyethylene glycol, cellulose derivatives, polyacrylamide, and sodium dodecyl sulfate.
7. The method for preparing an ebullated bed hydroprocessing catalyst according to claim 1, characterized in that: In the step (3), the injection rate of the sol B is 5 mL / min to 25 mL / min; the height of the oil layer is 2 / 3 to 3 / 4 of the total height of the oil layer and the alkaline solution layer; the drying temperature is 100°C to 150°C, and the drying time is 2 to 8 hours; the calcination temperature is 750°C to 900°C, and the calcination time is 2 to 6 hours.
8. The method for preparing an ebullated bed hydroprocessing catalyst according to claim 1, characterized in that: In the step (3), the oil in the upper layer is one of white oil and diesel, wherein the viscosity of the oil is 10 mm 2 / s~30mm 2 / s; The alkaline solution is one or more of ammonia water, ammonium carbonate, sodium hydroxide and potassium hydroxide solution, wherein the pH value of the alkaline solution is 10-12.
9. The method for preparing an ebullated bed hydroprocessing catalyst according to claim 1, characterized in that: In the step (4), the impregnation method is saturated impregnation or vacuum impregnation; the roasting temperature is 400-600° C.; the roasting time is 2-8 hours; and the active metal components are Mo, W, Ni and Co.
10. The method for preparing an ebullated bed hydroprocessing catalyst according to claim 9, characterized in that: In the step (4), the calcination temperature is 400-550°C.
Citation Information
Patent Citations
Boiling bed hydrogenation treatment catalyst and its preparing process
CN101240190B
Preparation method of tandem type inferior heavy oil fluidized bed hydrogenation catalyst
CN113663683A
Oil ammonia column shaping method of spherical aluminium oxide
CN1493524A
Boiling bed hydrogenation treatment catalyst and its preparing process
CN101240190A
Coal tar hydrogenation pretreatment catalyst and preparation method thereof
CN104549335A